PERANCANGAN SISTEM INFORMASI PENJUALAN BESI BERBASIS WEB PADA CV. MULYA JAYA YOGYAKARTA - Pudji Widodo; Khasanah Arum Wijayanti (Bianglala Informatika, 2020)
Today's information technology has developed very quickly. A fast, precise and accurate information system is needed now. CV. Mulya Jaya is a company engaged in the sale of building iron. During this time, employees are still having trouble making notes and sales reports that are still done manually. Therefore CV. Mulya Jaya really needs an information system that can help to simplify the process of making notes and sales reports.For this reason the researcher tries to make the Final Project on Designing Web-Based Iron Sales Information System on CV. Mulya Jaya Yogyakarta, which until now has not been computerized. Administration system CV. Mulya Jaya is currently still done manually. It is possible that there was an error during the process of making notes and sales reports. Design of Web-Based Iron Sales Information System in CV. Mulya Jaya Yogyakarta is one of the right and best solutions to solve a problem that exists in this company, and with a computerized system can achieve an appropriate, fast and accurate activity in supporting activities in this company.Keyword: Design, System, Information, Sales, Iron.